Understanding the Connection Between Common Stroke Comorbidities, Their Associated Inflammation, and the Course of the Cerebral Ischemia/Reperfusion Cascade - Przykaza, Łukasz (Frontiers in Immunology, 2021)
Despite the enormous progress in the understanding of the course of the ischemic stroke over the last few decades, a therapy that effectively protects neurovascular units (NVUs) and significantly improves neurological functions in stroke patients has still not been achieved. The reasons for this state are unclear, but it is obvious that the cerebral ischemia and reperfusion cascade is a highly complex phenomenon, which includes the intense neuroinflammatory processes, and comorbid stroke risk factors strongly worsen stroke outcomes and likely make a substantial contribution to the pathophysiology of the ischemia/reperfusion, enhancing difficulties in searching of succesfull treatment. Common concomitant stroke risk factors (arterial hypertension, diabetes mellitus and hyperlipidemia) strongly drive inflammatory processes during cerebral ischemia/reperfusion; because these factors are often present for a long time before a stroke, causing low-grade background inflammation in the brain, and already initially disrupting the proper functions of NVUs. Broad consideration of this situation in basic research may prove to be crucial for the success of future clinical trials of neuroprotection, vasculoprotection and immunomodulation in stroke. This review focuses on the mechanism by which coexisting common risk factors for stroke intertwine in cerebral ischemic/reperfusion cascade and the dysfunction and disintegration of NVUs through inflammatory processes, principally activation of pattern recognition receptors, alterations in the expression of adhesion molecules and the subsequent pathophysiological consequences.